Optineurin Functions for Optimal Immunity - Slowicka, Karolina; van Loo, Geert (Frontiers in Immunology, 2018)
Optineurin (OPTN) was identified 20 years ago in a yeast-two-hybrid screen with a viral protein known to inhibit the cytolytic effects of TNF. Since then, OPTN has been identified as a ubiquitin-binding protein involved in many signaling pathways and cellular processes, and mutations in the OPTN gene have been associated with glaucoma, Paget’s disease of bone and neurodegenerative pathologies. Its role in autophagy, however, has attracted most attention in recent years, and may explain (some of) the mechanisms behind the disease-associated mutations of OPTN. In this brief review we focus on the role of OPTN in inflammation and immunity and describe how this may translate to its involvement in human disease.